PENGARUH PEMBERIAN EDUKASI MELALUI MEDIA VIDEO ANIMASI TERHADAP PENINGKATAN PENGETAHUAN REMAJA PUTRI MENGENAI ANEMIA DI SMP PEMBANGUNAN PIYUNGAN - Putri, Kathy Ayu; Rusliani, Dian Monalisa; Issabella, Chentia Misse (NHM PRESS, 2025)
Anemia in adolescent girls is a health problem that affects growth and development, concentration in learning, and long-term productivity. The government has made efforts to prevent anemia through a policy of providing free iron tablets (TTD) and nutrition education in accordance with Law Number 17 of 2023 concerning Health which emphasizes the importance of promotive and preventive approaches. However, conventional education methods are considered less effective so that adolescent girls' awareness of anemia is still low. One alternative that is considered more effective is the use of animated video media as an educational tool. Objective: To determine the effect of providing education about anemia to female adolescents at Piyungan Development Middle School using animated video media. Method: This research is a type of quantitative research that uses a Pre Experimental research design using one group, which uses a one group pretest and posttest design. The population in this study were all female students in grades VII A, B and C at SMP Pembangunan Piyungan as many as 30 people, so the sample used in this study was 30 female students. Results: Education with animated video media is effective in increasing knowledge of adolescent girls about anemia. Before education, 76.7% of female students had poor knowledge, while after education, 83.3% had good knowledge. The Wilcoxon test showed a significant increase with a pretest score of 12.00 rising to a posttest of 19.80 (Z = 4.858, p < 0.05). Conclusion: Education with animated videos has been proven to be effective in increasing adolescent girls' knowledge about anemia, as shown by a significant increase in the knowledge category after the intervention.